Strategi Komunikasi Pariwisata Dalam Meningkatkan Kunjungan Wisatawan (2021) Melalui KEK Mandalika Lombok - Rahman, Ahmad Rofiki; Fajri, Choirul (Tuturlogi: Journal of Southeast Asian Communication, 2023)
The West Nusa Tenggara Province (NTB) Tourism Office is a government agency that manages all tourism activities in the NTB area. The NTB Dispar has implemented a strategy in the midst of the Covid-19 pandemic and during this pandemic there have been many changes in people's lives. In this study, the researcher discusses the communication strategy process implemented by the NTB Dispar in 2021, especially the strategy in the midst of the Covid-19 pandemic by focusing on one tourism destination that is currently global, namely the Mandalika Special Economic Zone. This research is a descriptive qualitative research with a case study approach. The results of this study indicate that in an effort to increase tourist visits in the midst of the Covid-19 pandemic, Dispar NTB implements a tourism communication strategy through three stages, namely planning, implementation, and evaluation in the form of identifying the target audience, determining communication goals, designing messages, choosing communication channels. , allocate the total budget and determine the promotion mix so that it can increase the number of tourist visits to NTB and can improve the community's economy.